Metabolomics and chemical composition comparison of raw carabao and raw cow milk - Adlong, Marc Joel G. (Animo Repository, 2022)
Ten biological samples of raw carabao milk and raw cow milk were collected to identify the metabolomic profiles, quantify cholesterol levels, and measure the pH levels of the two types of milk. Sample preparation via methanol-chloroform extraction followed by the addition of D2O and DSS was done before loading the samples in a JEOL 600 MHz NMR Spectrometer for analysis. After data preprocessing, PCA was performed and alongside Chenomx Profiler, a list of putatively identified metabolites was obtained. Results revealed that N,N-dimethylglycine was significantly higher in carabao milk, while glycolate and glycine were significantly higher in cow milk. Reverse-phase HPLC was used to quantify the cholesterol content in the milk samples that were extracted using diethyl ether-water extraction. A linear relationship between the cholesterol concentration and peak area was obtained with an r2 = 0.996; and an excellent percent recovery of 96.54 ± 3.85% was observed under optimized conditions. Results showed that at 95% confidence interval, there is no significant difference in the cholesterol content of carabao milk and cow milk which are observed to be 41.61 ± 28.28 ppm and 27.93 ± 11.87 ppm, respectively. Lastly, the pH analysis of the two types of milk revealed that both carabao milk and cow milk are slightly acidic with a mean pH of 6.60 ± 0.174 and 6.51 ± 0.120, respectively.